IMPLEMENTATION OF THE INTERNET OF THINGS (IoT) SYSTEM FOR THE COFFEE BEAN DRYING PROCESS USING A TRAY DRYER - Raihana, Raisa; Satriananda, S; Rihayat, Teuku (Jurnal Sains dan Teknologi Reaksi, 2025)
This study aims to implement an Internet of Things (IoT) system in the coffee bean drying process using a tray dryer to improve efficiency and ease of monitoring. The system is designed using a DHT22 sensor to read temperature and humidity, a MAX6675 sensor to monitor the heater temperature, an HX711 load cell sensor to measure the weight of the coffee beans, and a DS1302 RTC to record the drying time. All data is displayed on an LCD and sent to the Blynk IoT platform for remote monitoring. Testing was conducted with five drying temperature variations, namely 30°C, 35°C, 40°C, 45°C, and 50°C, each for 5 hours. The results showed that a temperature of 50°C produced the best results with a final moisture content of 7.21%, which meets the SNI 01-2907-2008 standard for coffee bean storage, which is a maximum of 12.5%. This IoT-based drying system has proven to be capable of automating the drying process with accurate and efficient monitoring, as well as enabling real-time remote monitoring. Thus, this system can be a modern solution in coffee post-harvest processing. Keywords: Blynk, coffee beans, drying, IoT, moisture content, sensors, tray dryer